Sodium grease formulation from waste engine oil - Nurul Waheeda, Abdu Rahman; Nur Suhaila, Anang Japar; Mohd Aizudin, Abd Aziz; Abdul Halim, Abdul Razik; Mohd Yusri, Mohd Yunus (IOP Publishing, 2019)
The present study was conducted to formulate sodium soap grease using waste engine oil (WEO). Greases were formulated by homogenizing sodium soap thickener in WEO for 2 hours at 150°C Different grease composition of oil-to-thickener ratio was designed which are 90/10, 80/20, 70/30 and 60/40. The formulated greases were analysed by conducting the consistency, oil bleeding, oil separation and FTIR characterization tests. The present study found that grease can be formulated using WEO and the thickener percentage have significant effect on formulated greases properties. Grease formulated with 70 – 80% of base oil and 20 – 30% of thickener was the best grease formulated as it shows desirable grease properties.